2020
DOI: 10.1186/s13058-020-01277-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptors are required effectors of TGFβ1-induced p38 MAPK signaling to advanced cancer phenotypes in triple-negative breast cancer

Abstract: Background Altered signaling pathways typify breast cancer and serve as direct inputs to steroid hormone receptor sensors. We previously reported that phospho-Ser134-GR (pS134-GR) species are elevated in triple-negative breast cancer (TNBC) and cooperate with hypoxia-inducible factors, providing a novel avenue for activation of GR in response to local or cellular stress. Methods We probed GR regulation by factors (cytokines, growth factors) that are rich within the tumor microenvironment (TME). TNBC cells har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…Among them, it was demonstrated that cellular stress, such as oxidative stress or hypoxia, in primary TNBCs or ERα-negative BC cell lines, increases the phosphorylation of GR on S134, thus potentiating stress signaling mediated by GR activation leading to an increase in the expression of breast tumor kinase BRK, known as protein tyrosine kinase 6 (PTK6), essential for aggressive BC phenotypes [ 115 ]. In addition, TNBCs express high levels of functionally active pS134-GR in comparison to luminal BCs, which could explain why GR expression is correlated with a better prognosis in luminal BCs than in TNBCs [ 116 ]. Recently, research on patients and TNBC cell line-derived xenograft models, revealed that GR activation at distant metastatic sites, due to an increase in GC levels, promotes BC colonization and reduces the overall survival by upregulating the expression of ROR-1 kinase, a receptor tyrosine kinase-like orphan receptor-1, previously shown to be implicated in BC [ 13 , 117 , 118 ].…”
Section: The Role Of Gr In Breast Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, it was demonstrated that cellular stress, such as oxidative stress or hypoxia, in primary TNBCs or ERα-negative BC cell lines, increases the phosphorylation of GR on S134, thus potentiating stress signaling mediated by GR activation leading to an increase in the expression of breast tumor kinase BRK, known as protein tyrosine kinase 6 (PTK6), essential for aggressive BC phenotypes [ 115 ]. In addition, TNBCs express high levels of functionally active pS134-GR in comparison to luminal BCs, which could explain why GR expression is correlated with a better prognosis in luminal BCs than in TNBCs [ 116 ]. Recently, research on patients and TNBC cell line-derived xenograft models, revealed that GR activation at distant metastatic sites, due to an increase in GC levels, promotes BC colonization and reduces the overall survival by upregulating the expression of ROR-1 kinase, a receptor tyrosine kinase-like orphan receptor-1, previously shown to be implicated in BC [ 13 , 117 , 118 ].…”
Section: The Role Of Gr In Breast Cancer Progressionmentioning
confidence: 99%
“…Moreover, they showed that in the absence of GR ligands, GR is transcriptionally activated in TNBCs through its phosphorylation on S134 by p38, following the homeostatic sensing of intrinsic stress or extrinsic factors (like TGFβ1). Phospho-S134-GR activates the p38 MAPK stress-signaling pathway, leading to TNBC cell anchorage-independent growth and migration [ 116 ].…”
Section: The Role Of Gr In Breast Cancer Progressionmentioning
confidence: 99%
“…These include S45, S113, S141, S203, S211, S226, S236, S267, S404, S134 and T8 and some of them are associated with inhibition of GC signalling [ 112 , 128 ]. A recent study on Triple-Negative Breast Cancer (TNBC) also showed that TGFβ promoted ligand-independent, p38 MAPK—induced S134 GR phosphorylation, which resulted in migration and invasion [ 129 ].…”
Section: Response To Stressmentioning
confidence: 99%
“…(Perez Kerkvliet et al 2020). Thus, targeting phospho-SR species may be possible using existing agents or newer, more selective SR antagonists paired with the appropriate MEK/MAPK or CDK signaling pathway inhibitors (Table 1).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%